1980
DOI: 10.1080/00913847.1980.11948563
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Junior Ice Hockey

Abstract: Does the price of a ticket entitle hockey fans to see more injuries? That's the result of excusing paid gate junior hockey players from wearing facial protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Player contact as the mechanism of injury in adolescent boys ranged from 12% to 48%, while the 1 study on girls reported that 58% of injuries were caused by player contact. 33 9-10 y 1.1/1000 h 0 1.0/1000 h 11-12 y 2.2/1000 h 0 1.8/1000 h 13-14 y 2.5/1000 h 10.9/1000 h 4.3/1000 h Brust et al (1992) 7 9-15 y 1/44 h 1/7 h Brust et al (1998) 8 11-14 y 106.4/1000 h Roberts et al (1999) 29 11-19 y 117.3/1000 h Gerberich et al (1987) 15 14-18 y 5.0/1000 h Park and Castaldi (1980) 24 15-19 y 1.57/game Pinto et al (1999) 26 16-20 y 4/1000 h 83/1000 h Stuart and Smith (1995) 31 17-20 y 3.9/1000 h 96.…”
Section: Injury Mechanismmentioning
confidence: 99%
“…Player contact as the mechanism of injury in adolescent boys ranged from 12% to 48%, while the 1 study on girls reported that 58% of injuries were caused by player contact. 33 9-10 y 1.1/1000 h 0 1.0/1000 h 11-12 y 2.2/1000 h 0 1.8/1000 h 13-14 y 2.5/1000 h 10.9/1000 h 4.3/1000 h Brust et al (1992) 7 9-15 y 1/44 h 1/7 h Brust et al (1998) 8 11-14 y 106.4/1000 h Roberts et al (1999) 29 11-19 y 117.3/1000 h Gerberich et al (1987) 15 14-18 y 5.0/1000 h Park and Castaldi (1980) 24 15-19 y 1.57/game Pinto et al (1999) 26 16-20 y 4/1000 h 83/1000 h Stuart and Smith (1995) 31 17-20 y 3.9/1000 h 96.…”
Section: Injury Mechanismmentioning
confidence: 99%
“…For junior level hockey athletes, the most prevalent injuries were facial lacerations, acromioclavicular (AC) sprains, and knee injuries, most often due to collisions. 30 , 65 , 76 , 77 , 84 , 87 …”
Section: Resultsmentioning
confidence: 99%
“…19,21,61 The most commonly injured position was forwards, followed by defenseman then goalkeepers. 38,42,46,48,56,65,66,71 Forwards are injured most commonly due to the elevated speed with which they play, and they are also commonly of smaller stature as compared with the defenseman against whom they are competing. Also, forwards are more commonly the position that receives a body check to disengage them from the puck as opposed to the defensive player who typically initiates contact.…”
Section: Discussionmentioning
confidence: 99%